2016
DOI: 10.1027/1192-5604/a000076
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Brain Hemodynamics in Response to Achromatic and Chromatic Cards of the Rorschach

Abstract: Abstract. In order to investigate the effects of color stimuli of the Rorschach inkblot method (RIM), the cerebral activity of 40 participants with no history of neurological or psychiatric illness was scanned while they engaged in the Rorschach task. A scanned image of the ten RIM inkblots was projected onto a screen in the MRI scanner. Cerebral activation in response to five achromatic color cards and five chromatic cards were compared. As a result, a significant increase in brain activity was observed in bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…Interestingly, the location of the temporo-parietal activation (Brodmann area [BA] 22) shown in the study is very close to the ROI in the superior temporal gyrus, which showed high significance in the fMRI study by Giromini, Viglione, Vitolo, et al (2019), suggesting that MNS might overlap with the neural network involving theory of mind. The participants were administered the Rorschach Test on a separate day from the fMRI experiment in the same procedure as is described in another report (Jimura, Konishi, Asari, et al, 2009). Following on from this published study, we have reanalyzed the imaging data to investigate whether movement determinants correlated with brain activity during understanding others' mental states (see Author Notes).…”
Section: Movement Determinantsmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, the location of the temporo-parietal activation (Brodmann area [BA] 22) shown in the study is very close to the ROI in the superior temporal gyrus, which showed high significance in the fMRI study by Giromini, Viglione, Vitolo, et al (2019), suggesting that MNS might overlap with the neural network involving theory of mind. The participants were administered the Rorschach Test on a separate day from the fMRI experiment in the same procedure as is described in another report (Jimura, Konishi, Asari, et al, 2009). Following on from this published study, we have reanalyzed the imaging data to investigate whether movement determinants correlated with brain activity during understanding others' mental states (see Author Notes).…”
Section: Movement Determinantsmentioning
confidence: 99%
“…To investigate whether there is a correlation between Sum C' and the brain activity associated with negative emotion, an fMRI study was conducted (Jimura, Konishi, Asari, et al, 2009) using the motion prediction task to evoke the brain activation associated with negative emotion. In this task, participants were required to predict whether a moving dot on the screen would reach the goal within the time limit.…”
Section: Achromatic Determinantsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, chromatic cards have been found to produce a higher number of responses, a longer reaction time, and to be evaluated as more pleasant or unpleasant than achromatic ones. They also tend to elicit more emotionally charged contents and have been found to be more likely to activate the left orbitofrontal cortex—widely involved in emotion regulation—than the achromatic cards (Ishibashi et al 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Results suggested positive effects of the amygdala on the relationship between the left anterior prefrontal and the right temporal pole and negative effects on the relationship between the right temporal pole and occipitotemporal regions. Ishibashi et al () examined the effects of color stimuli of RIM. As a result, in achromatic cords, a significant increase in brain activity was observed in relatively many areas, including the bilateral medial occipital gyrus, the bilateral pulvinars, and the right temporal gyrus, which were supposed to relate to attention to contour and shapes, while, in chromatic cards, a significant increase was observed in the left lingual gyrus and the left orbitofrontal cortex, which were considered to relate to color perception and its interference with visual processing.…”
mentioning
confidence: 99%